Reliability of heart period and systolic arterial pressure variabilities in women with fibromyalgia syndrome. Issue 9 (September 2016) - Andrade, Carolina; Zamunér, Antonio; Forti, Meire; França, Thalita; Silva, Ester
Abstract The aim of this study is to define absolute and relative reliability of spectral indices of cardiovascular autonomic control in the supine position in women with fibromyalgia syndrome (FMS). Twenty-three women with FMS (age 48 ± 7 years) took part in the study. ECG, finger blood pressure, and respiration were continuously recorded in all participants at rest in baseline 1 (BL1) and after 15 days from BL1 (BL2). The power spectrum analysis provided two oscillatory components: low frequency (LF, 0.04–0.15 Hz) and high frequency (HF, 0.15–0.4 Hz) from the heart period (HP) variability and the LF oscillatory component from SAP variability (LFSAP ). Absolute and relative reliability were rated by 95 % of the limit of random variation and intraclass correlation coefficient (ICC), respectively. No significant differences were observed between BL1 and BL2 for the spectral indices of HP and SAP variabilities. The 95 % limit of the random variation of these indices indicated that the values of repeated measurements were between 22 % higher and 0.2 % lower (more reliable parameter; average of HP variability) and 912.9 % higher and 0.2 % lower (less reliable parameter; LFSAP ) than BL1. Conversely, the index of relative reliability (ICC) ranged from 0.23 to 0.70 indicating a good reliability. The spectral indices of cardiovascular autonomic control in women with FMS seem to present good relative reliability. Therefore, these indices can be useful as parameters to quantify if a variation was consistent and accurate in the retest besides adding crucial information for clinical research and clinical evaluation of FMS patients.